PENGARUH MODEL PEMBELAJARAN RESOLUSI KONFLIK TERHADAP PRESTASI BELAJAR IPS DENGAN KOVARIABEL SIKAP MULTIKULTUR DAN EFIKASI DIRI PADA MAHASISWA PGSD UNDIKSHA - Ni Nyoman Lisna Handyani (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
This study aimed to assess the effect of learning model of conflict resolution on the learning achievement IPS with covariable multicultural attitude and self efficacy. Quantitative research was conducted in Ganesha Education University student PGSD using the experimental method to the design of single factor independent groups design with use of covariate and included 67 students. Data were analyzed by analysis of covariance (ANACOVA). The results showed that: 1) There are differences in social studies achievement between students who attend the learning model of conflict resolution and the students who attend conventional learning. 2) There are differences in social studies achievement between students who attend the learning model of conflict resolution and students who follow conventional teaching with multicultural attitude control. 3) There are differences in social studies achievement between students who attend the learning model of conflict resolution and students who follow conventional teaching by controlling the self-efficacy. 4) There are differences in social studies achievement between students who attend the learning model of conflict resolution and students who follow conventional teaching by controlling a multicultural attitude and self efficacy simultaneously. 5) There is a multicultural contributions attitude towards learning achievement IPS. 6) There is a self-efficacy contributes to learning achievement IPS. 7) There is contributing simultaneously, multicultural attitude and self efficacy of learning achievement IPS.